Pengaruh Kualitas Sumber Daya Pelatih Dan Admin Klub Terhadap Motivasi Pengembangan Pemain Internal Persebaya Amatir - Meisya Rahmatia Zefania; Supriyono Supriyono (Pakis Journal Institute, 2024)
This research aims to investigate the influence of the quality of coach and football club administration resources. A qualitative method with a descriptive approach is used to gain in-depth insights into the factors affecting player development. The study involves participants from several football clubs, utilizing in-depth interview techniques, observations, and document analysis. Data analysis is conducted by identifying patterns of findings, comparing interview results, and compiling detailed descriptions. The main findings indicate that the quality of coach resources, including tactical and technical knowledge, communication skills, and leadership, significantly impacts player motivation. Additionally, the quality of club administration, encompassing effective management, providing adequate facilities, and team coordination, also plays a crucial role in player development. This study provides a better understanding of the complex dynamics among these factors and highlights the importance of human resource management in the context of football player development. Practical implications of this research include recommendations for improving training quality, administrative management, and psychological support to enhance motivation and success in player development within football clubs.